2012
DOI: 10.1016/j.jhep.2011.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Non invasive evaluation of portal hypertension using transient elastography

Abstract: The development of portal hypertension is a common consequence of chronic liver diseases leading to the formation of esophageal and gastric varices responsible for variceal bleeding, associated with a high mortality rate, as well as other severe complications such as portosystemic encephalopathy and sepsis. Measurement of hepatic venous pressure gradient (HVPG) and upper GI endoscopy are considered the gold standards for portal hypertension assessment in patients with cirrhosis. However, both types of investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
227
2
7

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 291 publications
(244 citation statements)
references
References 78 publications
8
227
2
7
Order By: Relevance
“…Indeed, in the training set, 14 patients (10.6%) originally evaluated were excluded due to technical failure of transient elastography, confirming previous observations. 19 New transient elastography probes (XL probe), as well as new sonoelastography methods, might overcome this limitation of transient elastography, 34 with the added advantage of improving the applicability of measurement of spleen stiffness, which is emerging as a novel noninvasive parameter closely correlating with HVPG and presence of EVs. 35,36 Second, the prevalence of EVs in our population of compensated patients was relatively low, which might represent a bias for the generalizability of our results 37 ; however, the prevalence of varices in the validation cohort was exactly as anticipated.…”
Section: Clinical Livermentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, in the training set, 14 patients (10.6%) originally evaluated were excluded due to technical failure of transient elastography, confirming previous observations. 19 New transient elastography probes (XL probe), as well as new sonoelastography methods, might overcome this limitation of transient elastography, 34 with the added advantage of improving the applicability of measurement of spleen stiffness, which is emerging as a novel noninvasive parameter closely correlating with HVPG and presence of EVs. 35,36 Second, the prevalence of EVs in our population of compensated patients was relatively low, which might represent a bias for the generalizability of our results 37 ; however, the prevalence of varices in the validation cohort was exactly as anticipated.…”
Section: Clinical Livermentioning
confidence: 99%
“…While the accuracy of LS in predicting CSPH seems good, its discriminative ability in the prediction of EVs appears inadequate. 19 The combination of different methods might ameliorate the accuracy of single tests by assessing different pathophysiological components of portal hypertension. Recently, the combination of 3 simple methods-LS, spleen size, and platelet count (LSPS)-in a single score showed high accuracy for diagnosing and ruling out EVs in patients with compensated hepatitis B virusϪrelated chronic liver disease 20 ; however, this score has not been tested for the prediction of CSPH and there are no data on its ability to identify varices in patients with different etiologies of liver disease.…”
mentioning
confidence: 99%
“…The most commonly used method has been vibration-controlled transient elastography (TE) (FibroScan®; Echosens, Paris, France). LSM-TE has been extensively studied in the prediction of large varices with some variability in the results but in most studies showing a negative predictive value (NPV) above 90% (19)(20)(21). Nevertheless, studies were highly heterogeneous and this made it difficult to establish a defined threshold value that could be used to triage patients not needing endoscopy.…”
Section: Non-invasive Methods For the Detection Of Vntmentioning
confidence: 99%
“…Liver stiffness is an independent predictor of hepatocellular carcinoma (HCC) outcome [24] . A number of recent studies have shown that transient elastography correlates well with HVPG [12,25] . These tests may be more predictive of post resection outcomes [10] .…”
Section: Pressure Gradient In the Normal And Cirrhotic Livermentioning
confidence: 99%
“…There is the compensated stage, with a median survival of 12 years and the decompensated (variceal bleeding, hepatic encephalopathy and ascites) with a median survival of only two years [5] . In the cirrhotic patient, the hepatic venous pressure gradient, hepatic venous pressure gradient (HVPG) stands alone, in multiple logistic regression analysis, as the only independent variable predictive of post resection decompensation [6][7][8][9][10][11][12] . This pivotal role of HVPG is unexplained.…”
Section: Introductionmentioning
confidence: 99%